2010
DOI: 10.1366/000370210791114310
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the Thickness of Ultraviolet-Cured Pigmented Coatings and Printed Layers by Near-Infrared Spectroscopy

Abstract: Near-infrared (NIR) reflection spectroscopy was used for the determination of the thickness or the coating weight, respectively, of white-pigmented acrylic coatings and layers of printing inks. The thickness of coatings was studied in the range from 5 to 60 microm, whereas the coating weights of the printed layers covered a range between 1 to 5 g m(-2). Quantitative analysis of the spectral data relied on partial least squares (PLS) regression. A thickness gauge or gravimetry, respectively, were used to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Recently, an in-line monitoring method based on NIR reflection or transflection spectroscopy has been developed, and it was shown that it can be used for the direct determination of the coating thickness of acrylate coatings with thicknesses in the range of about 5 to 50 lm. [19][20][21][22] In printing technology, transparent lacquers are used as protective and decorative layers as well. In particular, they can be utilized for the creation of specific design effects on the print image.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an in-line monitoring method based on NIR reflection or transflection spectroscopy has been developed, and it was shown that it can be used for the direct determination of the coating thickness of acrylate coatings with thicknesses in the range of about 5 to 50 lm. [19][20][21][22] In printing technology, transparent lacquers are used as protective and decorative layers as well. In particular, they can be utilized for the creation of specific design effects on the print image.…”
Section: Introductionmentioning
confidence: 99%
“…The change in absorption of this CH oscillation is a direct measure of the degree of polymerization and accordingly an indicator for remaining acrylic C‐double bonds in the coating. Furthermore, an overall attenuation of the reflection is observed, as a result of the coating shrinkage in combination with a change of the refractive index,11, 12 and a change in molecular scattering. Consequently, a discrete measurement of the absorption at 1620 nm is only possible by compensating for these changes.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of sampling errors facilitates the study of the effect of: (1) scattering and depth of penetration, (2) the selection of spectral regions and (3) the effect of spectral preprocessing on the performance of the PLS models. <2 TF ternary fuel blends Rohe et al 21 <2 T polymer blends Heymann et al 13 <2 TF polymer film coatings Sulub and Derudder 22 <3 DR polymer blends Rosas et al 23 6.2 DR ternary mixture pellets Colón et al 24 2.5 DR pharm. powder blends Vanarase et al 25 7.5 DR pharm.…”
Section: Introductionmentioning
confidence: 99%
“…5 Nevertheless, NIR spectroscopy is considered as one of the most suitable and fast non-destructive methods for analysis of materials. NIR scattering is affected by physical differences of the materials, such as particle size, 69 density 1012 and thickness, 1315 This scattered radiation was studied using different numbers of layers of similar polymer sheets to describe the representative layer theory 16 and to find the absorption and remission fractions of layers which best fit the observed Log 1/R values. 17,18 In spite of the complexity of the interaction between radiation and particles, NIR spectroscopy is applied in many industries.…”
Section: Introductionmentioning
confidence: 99%